UPAYA MENINGKATKAN KEMAMPUAN BERBICARA ANAK MELALUI MEDIA BONEKA TANGAN PADA ANAK USIA 4-5 TAHUN DI RA HIDAYAT - Miskiyah, Zakiyatul; Eka Dheasari, Agustiarini (LPPM IAD Probolinggo, 2024)
The aim of the research is to be able to improve children's speaking skills through the media of hand puppets for children aged 4-5 years. The research was conducted at RA Hidayat which is located in RA Hidayat, Kanigaran, Probolinggi, Jawa Timur. The research method is PTK (Classroom Action Research) 2 cycles which includes students at RA Hidayat. The object of research is the ability to speak children. Data collection was carried out through observation techniques, interviews, as well as documentation where data analysis was carried out through qualitative descriptive. The results of the study showed that there was an increase in students' speaking skills after the practice of playing hand puppet media. The yield from the initial study was 31%; after the implementation of the action cycle I showed an increase in speaking ability by 59%; and finally, the results of the implementation of the second cycle of action showed an increase in speaking ability by 74%. In cycle I and cycle II, there was an increase in the child's ability to speak. Thus, learning and games through the media of hand puppets are effectively applied in pre-schools such as TK/RA in an effort to strengthen children's speaking skills. Keywords: Speaking Ability, Hand Puppet Media, Early Childhood